DEVELOPMENT OF PICTURED STORY BOOKS TO IMPROVE NUMERATION LITERACY AMONG PRIMARY SCHOOL STUDENTS AT SDN 002 TEBING CLASS III - Tasya Elmita; Fitria Meilina; Zulfiana Dessyka Putri; Anggri Dwi Nata (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research aims to develop and test the feasibility of picture story books as a medium for increasing numeracy literacy in class III students at SDN 002 Tebing. The research approach used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, and questionnaires conducted by a team of media experts, a team of material experts, teacher responses and testing the effectiveness of picture story books using pretests and posttests. The results of the development showed that the designed picture story book met the validity criteria of media experts and got an average score of 87% with a very feasible category. Material experts got an average score of 90% with a very feasible category and teacher response assessment got an average score of 89.333% with a very feasible category. Then the results of the effectiveness test using the N-Gain formula with a small group trial with an average score of 0.714 with a high category then a large group trial got an average score of 0.77 with a high category. It can be concluded that the developed picture story book is very feasible and effective as a learning medium to improve the numeracy literacy of grade III students at SDN 002 Tebing.